FORMULASI KRIM ANTIOKSIDAN EKSTRAK DAUN KAPAS (Gossypium sp.) - Hasniar Hasniar; Yusriadi Yusriadi; Akhmad Khumaidi (Universitas Tadulako, 2015)
Gossypium sp. leaf is one of the plants that contain flavonoids that can act as antioxidants. This study aims to look at the effect of combination of the stearic acid and triethanolamine which function as emulsifier in creams and determine antioxidant activity of cream Gossypium sp. leaf extract. Cream is formulated with a variety of stearic acid and triethanolamine emulsifier that F1 (8%: 2%), F2 (12%: 3%), F3 (16%: 4%). Tests carried out at the first day and the 28th days. Evaluation preparations include organoleptic test, homogeneity, viscosity, pH, and type of the cream. The results showed that the variation of concentration emulsifier that fill quality preparations with some parameters such as organoleptic, homogeneity, the type of cream and viscosity. pH of cream does not qualify are 4.5-6, but still in the neutral pH range (pH ± 7). Antioxidant activity of the cream has a large reduce power at the first day DPPH reduce percent value for F1, F2, and F3 are 80,73%, 83,05% and 83,51% respectively, while after the storage at the 28th days DPPH reduce percent value for F1, F2, and F3 are 80,43%, 82,49% and 79,02% respectively. Preparation creams that fill physical quality cream is F1 by using emulsifier triethanolamine and stearic acid with a concentration of 8%: 2%